Extreme Air Pollution Events Spiking Ionic Levels at Urban and Rural Sites of Indo-Gangetic Plain - Manisha Mishra; U. C. Kulshrestha (Aerosol and Air Quality Research)
Abstract The present study is a modest attempt to quantify the water-soluble inorganic ions (WSIIs) in the early morning (fog-forming) ambient air on the central Indo-Gangetic Plain (IGP) during winter via dissolution using a low-cost refluxing mist chamber. The chemical composition of the bulk samples showed significant differences in the WSIIs between the two monitored sites, one urban and the other rural, with NH4+ (47% and 37%, respectively) and Ca2+ (18% and 8%, respectively) being the major cations and NO3 (10% and 16%, respectively) and SO42− (9% and 14%, respectively) being the major anions. The WSII concentration spiked during November at both locations (∑WSII = 159.6 and 141.9 µg m−3) due to two extreme air pollution events, viz., i) the burning of crop residue and ii) the Diwali festival. These changes, which were corroborated by observations of the meteorological conditions, played an essential role in the wintertime atmospheric chemistry. On foggy days, significant scavenging of ions associated with crustal dust (Ca2+, Na+, Mg2+ and Cl −) occurred, although the ambient concentrations of other species (K+, NH4+, NO2, NO3 and SO42) remained relatively unaffected. Furthermore, the relationship between the cations and anions demonstrated that NH3 and HONO, as the primary gaseous species, were involved in heterogeneous aqueous-phase reactions and the formation of secondary aerosols. Source apportionment based on principal component analysis and the mass ratios also indicated that local anthropogenic sources, in addition to natural ones such as soil/road dust and biogenic emissions, influenced the WSII composition. Vehicular exhaust, solid waste and biofuel burning were identified as the major contributors of WSIIs at the urban site, whereas biomass burning, agricultural activity and coal combustion in brick kilns were the predominant sources at the rural site.